Assessment and Analysis of Resource Approach to Formation of Strategic Potential of Economy of the Region - Durdyeva, Dzhennet A.; Taran, Oleg L.; Aslanov, Dmitry I.; Bindasova, Natalya A.; Borlakova, Mariyam I. (International Review of Management and Marketing, 2016)
The present article offers the developed and proposed factorial estimation model for the total potential of the enterprise sector (in the region), including six factors describing the aggregate economic potential of the region as a set of conditions, resources and factors ensuring the reproduction process in it, depending on their level of internalization and recycling. Results of the study allow to systematize all existing approaches to the factors of production, as well as to improve these approaches according to the priority factor, effective usage of which streamlines branch structure of regions, reproductive and technological structure of capital investments and fixed assets, enhances the effectiveness of fixed capital. Keywords: regional economy, locality management system, labor resources JEL Classifications: P25; J53